PENGARUH GAYA KEPEMIMPINAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KERJA SEBAGAI VARIABLE INTERVENING PADA PT. KARUNIA JAYA GLOBAL - Prasetya, GL Hery; Hendarto, Rizki Tri (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2024)
This research aims to determine leadership style and compensation on employee performance through work motivation as an intervening variable at PT. Karunia Jaya Global. The sample used in this research was employees of PT. Karunia Jaya Global has a sample size of 55 employees. Based on the hypothetical test results in Sub Structure Path Analysis 1, the results showed that leadership style and compensation had a direct positive and significant effect on work motivation. Meanwhile, the results of hypothesis testing in Sub Structure Path Analysis 2 showed that leadership style, compensation, and work motivation had a direct positive and significant effect on employee performance. Likewise, leadership style and compensation positively and significantly indirectly affect employee performance through work motivation as an intervening variable.